Detection of Cryptosporidium spp. in Wild Rats (Rattus spp.) in Surabaya, East Java - Pratama, Ponasari Galuh; Suprihati, Endang; Suwanti, Lucia Tri; Mufasirin; Hastutiek, Poedji; Setiawan, Boedi; Puspitasari, Heni; Indasari, Elly Nur (Universitas Airlangga, 2024)
Cryptosporidiosis is a waterborne zoonosis caused by Cryptosporidium, which is a parasite that causes infection of the small intestine and leads to acute diarrhea in both humans and animals. Wild rats (Rattus spp.) are known to carry many zoonotic pathogens including Cryptosporidium. Given their close proximity to humans in urban environments, the likelihood of disease transmission is high. This study aims to detect the Cryptosporidium spp. infection in wild rats in Surabaya City, East Java Province. Intestinal fecal samples were collected using necropsy. The flotation test and Ziehl-Neelsen stain were used to observe the presence of Cryptosporidium under the microscope. The results showed that 69 samples were positive for Cryptosporidium spp. in the oocyst stage, which appeared dark pink with a clear cavity and the size of the oocysts ranged from 2-6 Î¼m. The high incidence of cryptosporidiosis in wild rats is a potential health threat to both animals and humans.